Unresolved haemosporidia of the Australian skink, Egernia stokesii - Zechmeisterová, Kristína; Gardner, Michael George; Široký, Pavel (Parasitology research, 2024)
The Australian skink Egernia stokesii had been recognised as a host of two species of Plasmodium, Plasmodium mackerrasae and P. circularis; nevertheless, molecular data are available for only a single haemosporidian species of this host. Its sequences are labelled as "Plasmodium sp." or "Plasmodium mackerrasae", but morphological characteristics of this isolate are unavailable. Phylogenetic analyses of these sequences placed them into the clade of the genus Haemocystidium. In this study, blood samples of six E. stokesii were analysed by both, molecular and microscopic methods to clarify the haemosporidia of this lizard. Application of these approaches offered discordant results. Whereas sequence analysis clustered our isolates with lizard species of Haemocystidium, morphology of blood stages is more akin to Plasmodium than Haemocystidium. However, limited sampling, indistinguishable nuclei/merozoites and risk of possible hidden presence of mixed infection prevent reliable species identification of detected parasites or their description as new species of Haemocystidium.
Keywords: Haemocystidium; Animals; Plasmodium mackerrasae; RNA, Ribosomal, 18S; ribozomální DNA; DNA, Ribosomal; Protozoan Infections, Animal; krev; Australia; Lizard; shluková analýza; Molecular Sequence Data; Blood; Egernia stokesii; Austrálie; Phylogeny; molekulární sekvence - údaje; DNA, Protozoan; protozoální DNA; Lizards; RNA ribozomální 18S; Sequence Analysis, DNA; Haemosporidia; protozoální infekce zvířat; Haemosporida; ještěři; zvířata; sekvenční analýza DNA; Cluster Analysis; fylogeneze; mikroskopie; Microscopy